H15 Let us talk: a communication skills training course for Russian healthcare professionals working with Huntington's disease. (12th September 2022) - Júlio, Filipa; Arnesen, Astri; Schepper, Beatrice De; Sousa, Dina De; Lis, Danuta; Oblitsova, Julia; Olsen, Svein Olaf; Papantoniou, Giorgos; Ristolainen-Kotimäki, Saija; Tretyakova, Marina; Umakhanova, Zaynab; ,
Abstract : Background: The relationship between premanifest and potential carriers of Huntington's Disease (HD) and healthcare professionals presents some challenges in Russia. Accordingly, the European Huntington Association (EHA) developed 'Let Us Talk', a web-based course to train professionals on ways to effectively communicate and relate to HD families. Aims: This work aimed to assess the impact of 'Let Us Talk' on the communication skills of the course participants. Methods: The online training was implemented over three Saturdays (12 hours). Russian and non-Russian HD experts addressed topics such as verbal/non-verbal communication or HD-related communication changes. Original learning formats were used, like the screening of interviews with HD families. The EHA created a 20-item online questionnaire about communication skills in clinical settings, which was administered at the beginning of the training and one month later. The results of the two measurements were compared. Results: 111 Russian healthcare professionals attended the course (79.2% neurologists). 59 answered the questionnaire at baseline and 30 answered it one month later. Significant differences were found in the behaviours adopted before and after the training. There was a decreased use of medical jargon and an increased recognition of the importance of giving patients' time to express their questions and concerns. Conclusions: 'Let Us Talk' seems to have improved the communication skills of Russian healthcare professionals, who reported more appropriate behaviours towards HD families after the course. This training appears to be a good model for the EHA to replicate in other countries and enhance the doctor-HD patient relationship across Europe.